Abu Zayd Al-Balkhi's Perspective on Depression: Countering Sadness with Cognitive Theory in the Book of Mashalih al Abdan wa al Anfus - Jarman Arroisi; Novita Najwa Himaya (Fakultas Psikologi UIN Syarif Hidayatullah Jakarta, 2023)
Depression is one of the most common mental illnesses today. Due to the considerable influence of depression in daily activities, sufferers experience deep sadness and grief and even take solutions by suicide. Although some doctors and psychologists have presented many solutions, depression is still a rampant mental illness at any time. In this case, a Muslim psychologist of Afghanistan origin named Abu Zayd Al-Balkhi, explained the various causes of depression followed by its symptoms and factors. Not spared from symptoms and factors, Al Balkhi also explained the steps and solutions for people with depression. The method used by Al-Balkhi that has never been done by Muslim psychologists before is with cognitive theory. Regarding depression, Al Balkhi's discussion was supported by earlier Islamic scholars who also wrote in his work on the prevention of grief (depression). This study used a literature study by collecting data and information on the importance of depression prevention and how to treat people with depression. The results of this study explain how important a person is in enduring feelings of sadness and loss that will result in depression.